Anti-stacking dense conversion of solid organic sodium salt particles into graphene with excellent electrode performance1. Issue 71 (2nd August 2015) - Cui, H. J.; Zhu, Y. Y.; Zheng, J. F.; Jia, S. P.; Wang, Z. J.; Zhu, Z. P.
<x xml:space="preserve">Abstract</x> Graphene frameworks can be densely synthesized from a rapid decomposition of common solid organic sodium salts.